2019
DOI: 10.1038/s41395-018-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Acute Chronic Liver Failure in Patients With Cirrhosis Undergoing Endoscopic Retrograde Cholangiopancreatography: A Multicenter Matched-Cohort Study

Abstract: The rate of AEs after ERCP is higher in patients with cirrhosis compared to the non-cirrhotic population. The incidence of ACLF is higher in those with AEs after ERCP compared to those without AEs, especially cholangitis. The development of ACLF is common after ERCP and other invasive procedures. ACLF can be precipitated by numerous factors which include preceding events before the procedure, including manipulation of the bile duct, and AEs after an ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
2
30
1
1
Order By: Relevance
“…This finding adds to a growing body of research suggesting that only Child-Pugh class C is truly predictive of adverse events[5,8,9]. The implication that MELD-Na may be a more useful predictive tool is particularly notable as our review of the literature found that only a few studies evaluated MELD-Na score when examining outcomes of interventional GI procedures in patients with cirrhosis[6].…”
Section: Discussionmentioning
confidence: 76%
“…This finding adds to a growing body of research suggesting that only Child-Pugh class C is truly predictive of adverse events[5,8,9]. The implication that MELD-Na may be a more useful predictive tool is particularly notable as our review of the literature found that only a few studies evaluated MELD-Na score when examining outcomes of interventional GI procedures in patients with cirrhosis[6].…”
Section: Discussionmentioning
confidence: 76%
“…With respect to post-sphincterotomy bleeding (PSB), risk factors mentioned in the above recommendation are independent and were evidenced in at least two of 10 studies summarized in Table 2s. Cirrhosis was confirmed as a risk factor in a meta-analysis (6 studies, 5526 patients) [39] and in a more recent matched cohort retrospective study (331 patients) [40]. Dialysis for end-stage renal disease was associated with PSB in all four casecontrol studies (7508 cases vs. 450 246 controls) on the topic (OR 1.4, 95 %CI 1.2 -1.6 in the largest study) [36,37,41,42], and particularly year-long hemodialysis [43].…”
Section: Risk Factors For Post-sphincterotomy Bleedingmentioning
confidence: 89%
“…The risk of ACLF was significantly higher in those with greater hepatic decompensation (Model for End‐Stage Liver Disease score ≥15) at baseline. The occurrence of ACLF after ERCP was driven by adverse events, particularly cholangitis . Regardless of the invasive procedure, it appears that diligent assessment of hepatic reserve should be completed prior to any treatment, in an effort to prevent the development of ACLF.…”
Section: Invasive Proceduresmentioning
confidence: 99%